Factors Determining Work Participation and Labour Supply Decisions in Pakistan's Urban Areas (The Pakistan Development Review, 1990)
Labour force participation in PClkistan, even amongst prime-aged males, is lower than observed in many similar countries. The analysis of labour force participation in urban PClkistan in this paper indicates that systematic factors explain a fair amount of this participation. The extended family structure as well as the availability of remittances allow younger, educated males to extend their job search. Using tobit and probit estimation techniques, the study found that labour supply is explained primarily by participation as opposed to hours worked con~tional upon participation. The study also found that the rise in wages attributed to education is fairly high and similar to what was found in Pakistan in the late 1970s.